Causal link between mental disorders and gastrointestinal diseases: a Mendelian randomization study - Ding, Wenjing; Chen, Liangliang; Pei, Bei; Gao, Dahong; Xia, Jianguo; Li, Xuejun; Wang, Yougang (Frontiers in Endocrinology, 2025)
BackgroundObservational research suggests that mental diseases may increase the risk of gastrointestinal diseases. However, the causal link between these conditions remains unclear. In this study, we conducted a two-sample Mendelian randomization (MR) analysis to investigate the causal associations between common mental diseases and the risk of gastrointestinal diseases.MethodsFirst, a series of parameters were set to select single-nucleotide polymorphisms (SNPs) from genome-wide association studies (GWAS). Second, A two-sample Mendelian randomization analysis was conducted to investigate the causal link between mental diseases (Alzheimer’s disease, depression, major depressive disorder, Parkinson’s disease, schizophrenia) and gastrointestinal diseases (gastritis and duodenitis, gastric cancer) while removing outliers using MR-PRESSO. Finally, eight methods of MR analysis were used to generate forest plots, including inverse variance weighted (IVW), inverse variance weighted (fixed effects) (IVW fixed effects), maximum likelihood (ML), MR-Egger, weighted median, penalized weighted median, simple mode, and weighted mode, with IVW considered the primary method.ResultsThe result demonstrated that most MDs have no evidence of a causal link between gastrointestinal diseases except Parkinson’s disease and gastric cancer based on the IVW method (OR = 0.929 [95% CI = 0.869–0.992], p = 0.029). Subsequently, we performed a robustness analysis to ensure consistency.ConclusionsOur method provided evidence supporting a causal link between Parkinson’s disease and the risk of gastric cancer. However, no evidence was found for other mental diseases influencing the risk of gastrointestinal diseases. Further research is warranted to explore how mental diseases affect the development of gastrointestinal diseases.